2004
DOI: 10.1038/sj.embor.7400153
|View full text |Cite
|
Sign up to set email alerts
|

Processed caspase‐2 can induce mitochondria‐mediated apoptosis independently of its enzymatic activity

Abstract: The mechanism by which caspase-2 executes apoptosis remains obscure. Recent findings indicate that caspase-2 is activated early in response to DNA-damaging antineoplastic agents and may be important for the engagement of the mitochondrial apoptotic pathway. We demonstrate here that fully processed caspase-2 stimulates mitochondrial release of cytochrome c and Smac/ DIABLO, but not apoptosis-inducing factor (AIF). This event occurs independently of several Bcl-2 family proteins, including Bax, Bak and Bcl-2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 23 publications
10
104
2
1
Order By: Relevance
“…Moreover, As 2 O 3 -induced cell demise was not blocked in cells deficient for caspase-2 or -9. While caspase-9 is part of the apoptosome and therefore plays a key role during the mitochondrial pathway of apoptosis (Hu et al, 1999;Saleh et al, 1999;Zou et al, 1999), caspase-2 is currently discussed as an initiator caspase that might respond to DNA damage and activates the mitochondrial apoptosis machinery (Troy and Shelanski, 2003;Norbury and Zhivotovsky, 2004;Robertson et al, 2004). Nevertheless, our present data delineate that caspases appear to be dispensable for induction of cell death by As 2 O 3 .…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, As 2 O 3 -induced cell demise was not blocked in cells deficient for caspase-2 or -9. While caspase-9 is part of the apoptosome and therefore plays a key role during the mitochondrial pathway of apoptosis (Hu et al, 1999;Saleh et al, 1999;Zou et al, 1999), caspase-2 is currently discussed as an initiator caspase that might respond to DNA damage and activates the mitochondrial apoptosis machinery (Troy and Shelanski, 2003;Norbury and Zhivotovsky, 2004;Robertson et al, 2004). Nevertheless, our present data delineate that caspases appear to be dispensable for induction of cell death by As 2 O 3 .…”
Section: Discussioncontrasting
confidence: 53%
“…To determine whether the pan-caspase inhibitor BAF influenced caspases upstream of cytochrome c release, similar to in vitro studies (Lassus et al, 2002;Li et al, 1998;Robertson et al, 2004), cytosolic caspase-2 and caspase-8 proteolysis were evaluated 24 h after CCI in rats treated with 1000 nmol BAF or vehicle. Consistent with a regulatory role for caspase-2 in mitochondrial cytochrome c release, BAF treatment reduced caspase-2 proteolysis in ipsilateral cortex by > 50% compared with vehicle treatment, and also reduced caspase-2 proteolysis in ipsilateral hippocampus, but to a lesser degree than in cortex (Figures 3A and 3B; P < 0.05, t-test).…”
Section: Boc-aspartyl(ome)-fluoromethylketone Reduces Caspase-2 But Nmentioning
confidence: 99%
“…Recently, initiator caspases have been shown to be upstream regulators of cytochrome c release from the mitochondria. Under conditions of cell stress, caspase-2 permeabilizes the outer mitochondrial membrane facilitating cytochrome c release, an event requiring caspase-2 proteolysis but independent of its enzymatic activity (Lassus et al, 2002;Robertson et al, 2004). Activated caspase-8 can also result in cytochrome c release via truncation of the proapoptotic Bcl-2 family member Bid, with translocation of truncated Bid (tBid) into mitochondria (Henshall et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that caspase-2 plays a prominent role in different cell death systems (reviewed by Degterev et al, 2003) including the release of apoptogenic factors from mitochondria directly (Guo et al, 2002;Lassus et al, 2002). It is interesting that processed caspase-2 can induce mitochondria-mediated apoptosis independent of its enzymatic activity (Robertson et al, 2004).…”
Section: Androgen-regulated Apoptosis By Tnfr Family Ligands Ow Rokhlmentioning
confidence: 99%